The Mythical Foundation of Money and its Early Moments of Abstraction. Connections Between Georg Simmel and Ernst Cassirer - Klattenhoff, Timo (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2017)
Are there similarities between Georg Simmel's concept of money in its early stages and Ernst Cassirer's works on myth as a symbolic form? To answer this question, this paper discusses parts of Simmel's “Philosophy of Money” and Cassirer's “Philosophy of Symbolic Forms”: By showing how primeval use of objects which carry monetary characteristics can be parallelized with ways of mythic world interpretation, similarities between Simmel's and Cassirer's arguments can be highlighted. It is not only the mind, which gains the ability of abstract thinking their examples and concepts point to, but also an idea of culture, which reflects this development.